2018
DOI: 10.3390/sym10080307
|View full text |Cite
|
Sign up to set email alerts
|

On the Computation of the Dispersion Diagram of Symmetric One-Dimensionally Periodic Structures

Abstract: A critical discussion on the computation of the dispersion diagram of electromagnetic guiding/radiating structures with one-dimensional periodicity using general-purpose electromagnetic simulation software is presented in this work. In these methods, full-wave simulations of finite sections of the periodic structure are combined with appropriate simplifying network models. In particular, we analyze the advantages and limitations of two different combined methods, with emphasis on the determination of their ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…In this work, all the dispersion analyses were carried out using the Eigenmode solver in CST Microwave Studio considering periodic boundaries in x-and y-directions, and electrical boundaries in the z-direction. Although there are available methods to quickly analyze glide symmetry based on the Floquet theorem [12][13][14] or equivalent circuits [11,29], these methods were not proposed to analyze this structure [30]. The dispersion diagrams only represent phase variations in the y-direction, as it is the direction in which the glide symmetry takes place.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, all the dispersion analyses were carried out using the Eigenmode solver in CST Microwave Studio considering periodic boundaries in x-and y-directions, and electrical boundaries in the z-direction. Although there are available methods to quickly analyze glide symmetry based on the Floquet theorem [12][13][14] or equivalent circuits [11,29], these methods were not proposed to analyze this structure [30]. The dispersion diagrams only represent phase variations in the y-direction, as it is the direction in which the glide symmetry takes place.…”
Section: Methodsmentioning
confidence: 99%
“…In [26], this assumption is shown to be valid as long as d > p/2. In [29], the validity is more correctly stated in terms of higher-mode relevance. In this sub-section, we class glide-symmetric structures in two kinds, and relate this classification with the nature of the modal interaction between adjacent cells.…”
Section: B Reducible and Irreducible Glide Structuresmentioning
confidence: 97%
“…Under the assumption that each corrugation can be replaced by Marcuvitz's closed-form equivalent circuit [28], it was easily shown that the glide symmetry effect is equivalent to simply halving the spatial period. The study in [29], discussing reduced representations of several kinds of higher-symmetric periodic lines proposed in [30], has recently shown that a more correct condition for this conclusion is to neglect interactions due to localized excitation of higher-order waveguide modes.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of the parallel plate stopband were carried out by calculating the dispersion diagram of a unit cell using the commercial software CST Microwave Studio. Alternative methodologies for calculating dispersion diagrams of these kinds of structures were presented in [20].…”
Section: Stopband Analysismentioning
confidence: 99%